Wage and Productivity Dispersion in U.S. Manufacturing: The Role of Computer Investment - Timothy Dunne; Lucia Foster; John Haltiwanger; Kenneth R. Troske (Institute for the Study of Labor (IZA), 2002)
By exploiting establishment-level data, this paper sheds new light on the sources of the changes in the structure of production, wages, and employment that have occurred over the last several decades. We investigate the following two related hypotheses. First, that most of the recent increase in the dispersion of wages and productivity has occurred across establishments and these changes are linked. Second, that the increased dispersion in wages and productivity across establishments is linked to differential rates of technological adoption across establishments. Our findings are largely supportive of these hypotheses. Specifically, we find that (1) the between-plant component of wage dispersion is an important and growing part of total wage dispersion; (2) much of the between plant increase in wage dispersion is within industries; (3) the between-plant measures of wage and productivity dispersion have increased substantially over the last few decades; and (4) a significant fraction of the rising dispersion in wages and (to a lesser extent) productivity is accounted for by changes in the distribution of computer investment across plants as well as changes in the wage and productivity differentials associated with the computer investment.
Keywords: J3; D3; 330; wages; productivity; dispersion; Lohnstruktur; Produktivität; Computergestütztes Verfahren; Datenverarbeitung; Verarbeitendes Gewerbe; Vereinigte Staaten